2014
DOI: 10.2478/s11535-014-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ELF-EMF on antioxidant status and micronuclei in K562 cells and normal lymphocytes

Abstract: The effect of ELF-EMF on DNA through changes in antioxidative enzyme activities has not been sufficiently explored yet. The aim of this study was to determine ELF-EMF effect on antioxidative enzymes in cancer cell line and genotoxic potential on normal human lymphocytes. K562 cells were exposed to 50 Hz ELF-EMF (40 μT, 100 μT; 3 h, 24 h) and spectrophotometric determination of lipid peroxidation and antioxidative enzyme activities was conducted. Genotoxicity of ELF-EMF (50 Hz, 100 μT) was investigated by cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, Srdjenovic et al 75 and Khavari et al 76 revealed ELF-EMF exposure in K562 cells (50 Hz, 100 μT, 24 h and 48 h) and DU145 cells (50 Hz, 0.6 mT, 24 h and 48 h) significantly increased cell proliferation. However, Yoshizawa et al showed that exposure of K562 cells to ELF-EMF at 500, 100, 20, and 2 µT intensity and 50 Hz, 60 Hz frequency during 24 h and 48 h does not affect cell proliferation 77 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Srdjenovic et al 75 and Khavari et al 76 revealed ELF-EMF exposure in K562 cells (50 Hz, 100 μT, 24 h and 48 h) and DU145 cells (50 Hz, 0.6 mT, 24 h and 48 h) significantly increased cell proliferation. However, Yoshizawa et al showed that exposure of K562 cells to ELF-EMF at 500, 100, 20, and 2 µT intensity and 50 Hz, 60 Hz frequency during 24 h and 48 h does not affect cell proliferation 77 .…”
Section: Discussionmentioning
confidence: 96%
“…These results accompanied by many others indicate that comprehensive studies to investigate wide range effects of different parameters of magnetic field-cells interaction are necessary 11,74 . www.nature.com/scientificreports/ Moreover, Srdjenovic et al 75 and Khavari et al 76 revealed ELF-EMF exposure in K562 cells (50 Hz, 100 μT, 24 h and 48 h) and DU145 cells (50 Hz, 0.6 mT, 24 h and 48 h) significantly increased cell proliferation. However, Yoshizawa et al showed that exposure of K562 cells to ELF-EMF at 500, 100, 20, and 2 µT intensity and 50 Hz, 60 Hz frequency during 24 h and 48 h does not affect cell proliferation 77 .…”
Section: K562 (Nonmentioning
confidence: 99%
“…A reaction mixture of catalase assay was prepared with 50 mM phosphate buffer (750 μ l), 15 mM H 2 O 2 (250 μ l), and 20 μ l cell Lysate. The absorbance of the reaction mixture was recorded at 240 nm for 1 min at 15 seconds intervals in both blank and test samples [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mixture containing 30 μ l cell Lysate, tris-HCl buffer (pH 8.2), 2 mM pyrogallol, 30 mM EDTA (250 μ l). The absorbance of the reaction mixture was recorded at 420 nm for 3 min at 30 seconds intervals in both blank and test samples [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“… 107 Furthermore, ELF‐EMF can enhance activity of both glutathione‐S‐transferase and ‐reductase enzymes in malignant cells. 108 Also, based on Cichon et al, 109 ELF‐EMF exposure can upregulate expression of different antioxidant target genes including CAT, SOD1, SOD2, GPx1 and GPx4. In addition, multiple pathways involved in orchestrating cellular stress response of cells to stressful condition can also become activated following ELF‐EMF exposure.…”
Section: Elf‐emf and Induction Of Cellular Stress Responsementioning
confidence: 99%